Investigating the potential of mirtazapine to induce drug-seeking behavior in free-choice drinking mouse model - Yusuf S. Althobaiti (Elsevier, 2022)
Addiction to various drugs and chemicals is a significant public health concern worldwide. Addiction to prescription medications has increased due to the psychoactive effects of these medications, their availability, low price, and the lack of legal consequences for abusers. One of such prescription medication is mirtazapine (MIRT). MIRT is an antidepressant that has recently been reported to be abused and could induce withdrawal symptoms in different case studies. No previous study has investigated its abuse potential in animal models of drug addiction. Here, we conducted a free-choice drinking paradigm to investigate voluntary drinking of MIRT at two different concentrations. Male BALB/c mice were given unlimited access to two water bottles for five days before being divided into three groups: the first group had free access to two water bottles. The second group (MIRT10) and the third group (MIRT20) was allowed unlimited choice to one bottle of water and one bottle of MIRT at concentrations of 0.03 and 0.06 mg/mL, respectively. The average daily MIRT intake in the MIRT20 group was significantly higher on all tested days than that in the MIRT10 group. Moreover, mice in the MIRT20 group preferred to self-administer MIRT over water, indicating that MIRT can induce drug-seeking behavior. To further investigate the addictive potential of MIRT and its possible deterioration of memory and recognition, as reported with several known drugs of abuse, animals underwent a novel object recognition test. Mice in the MIRT20 group demonstrated significant deterioration in memory and recognition, indicating its effects on different brain regions involved in recognition, similar to other known drugs of abuse. The forced swimming test and tail suspension test were used to test MIRT-induced withdrawal symptoms after forced abstinence. After eight days of abstinence, mice in the MIRT20 group demonstrated significant depression-like symptoms in both the TST and FST, manifested by a significant increase in immobility time. MIRT was shown to induce drug-seeking behavior, deteriorate recognition, and cause withdrawal symptoms. This might confirm that MIRT has the potential to induce drug dependence and further studies are warranted to explore the neurobiological basis of MIRT-induced drug-seeking behavior.